Ankylosing Spondylitis Complicated with Atlantoaxial Dislocation and Destruction of the Dens and Lateral Atlantoaxial Joint: A Case Report. Issue 4 (October 2019) - Shao, Jia; Gao, Yan Zheng; Gao, Kun; Yu, Zheng Hong
Abstract : Case: Non-neoplastic bone destruction, known as Andersson lesion, is not rare in ankylosing spondylitis (AS) and always appeared as bone destruction and sclerosis in the vertebral body-intervertebral disc region. The Andersson lesion has been reported mostly in the thoracic and lumbar spine and rarely in the lower cervical spine. We surgically treated a patient with AS complicated with atlantoaxial dislocation and destruction of dens and lateral atlantoaxial joint, which was similar to the Andersson lesion. Conclusions: AS can cause destructive lesion in the upper cervical spine. Posterior reduction, removal of the lesion, and fusion were possible approaches for the treatment of this destructive lesion.